Pengaruh ROI dan DER Terhadap Tax Avoidance - Berliana, Muthia; Mahpudin, Endang (Universitas Muhammadiyah Tangerang, 2021)
This study aims to determine the effect of ROI (X1), and DER (X2) on simultaneous and partial tax avoidance (Y). This research uses financial statements of companies food and beverage in the (IDX) periode 2018-2020, uses 19 companies. The results show that: (1) ROI has a partial no effect on tax avoidance, (2) DER has a partial effect on tax avoidance, and (3) ROI and DER simultaneously have an effect on tax avoidance.